ANALYSIS OF MENU AND MENU ENGINEERINGPLANNING IN PASTRY DEPARTMENTS IN MERCURE HOTEL JAKARTA SIMATUPANG - Ramzani, Rahma; Pranita, Diaz; Auliya, Annisatul (UI Scholars Hub, 2019)
This journal discusses about the analysis of menu planning and menu engineering in the pastry department at Mercure Hotel Jakarta Simatupang. The type of research used in this assignment is a descriptive research. The data collection techniques derived from interviews, observations and literature study through the online book. Those source of data becomes an element of description on the subject. The final research recommends Mercure Hotel Jakarta Simatupang to improve the strategy of menu planning and analysis on Karumba! Rooftop restaurant, which intended to improve the effectiveness and efficiency.